Ensino de astronomia e aprendizagem significativa: um olhar sobre o ensino técnico integrado do Instituto Federal de Minas Gerais - Campus São João Evangelist - Simões, Cleonir Coelho (2020)
This research has as main theme the Teaching of Astronomy and its objective was to investigate the occurrence of Meaningful Learning in a group of students of Integrated Technical Education at the Federal Institute of Minas Gerais, campus São João Evangelista, through a course on basic concepts of Astronomy. The course has hybrid characteristics and was based on the bibliography of the Brazilian Astronomy Olympiad, books and publications by researchers in the area. In addition, the course sought to integrate diversified methodologies and promote the use of digital technologies. The main theoretical framework adopted in the research was the Theory of Meaningful Learning. Data collection took place through questionnaires, participants' reports, direct observation and the audio and video recording of the various moments of the research. A pre-test and a post-test were performed, whose results were analysed and submitted to statistical tests to verify the occurrence of Meaningful Learning. The reports, observations and records in audio and video were used to qualitatively assess the various educational activities developed. It is, therefore, a mixed research, as it involved the collection and analysis of quantitative and qualitative data. As a result, indications of the occurrence of Meaningful Learning and the development of skills and competences related to Astronomy were identified. A positive evaluation of the various applied methodologies was also obtained. Finally, it is concluded that an intervention of this nature represents a potentially viable proposal to promote the Teaching of Astronomy in any educational institution and, above all, in the Federal Institute of Minas Gerais, São João Evangelista campus, the locus of the researc